Placebo Effect in Matter of Contemporary Self-Reward - Riza, Dwi Ainur; Margaretha, Sherlly; Kurniawati, Wiwin Anggraeni; Kartiningsih, Rindrah; Pasopati, Rommel Utungga (Proceeding International Conference on Religion, Science and Education, 2025)
This article underlines matter of placebo effect in self-reward done by youngsters in recent days. Contemporary self-reward is seen as a form of self-love to appreciate any hard work done by someone. It is being spread by social media that tend to give various examples of this action. The self-reward is done as actualization of me-time, relaxation, shopping, and even going abroad. However, that self-love is not essential since it only reflects matter of psychological illusions as seen in placebo effect. In analysis, through qualitative method and explorative approach, this paper accentuates that self-reward is such placebo effect. It may give relaxation, but it is only illusion since the main idea is to spend more and to be more consumptive. It only works as coincidences and suggestions that will promote more endorphin hormone, but not as the main love itself. In conclusion, self-reward as placebo effect may only work in surface as perceptions, but not as the essential point of self-indication in matter of love.